Arrhythmia and cardiomyopathy in Heritable Thoracic Aortic Disease: an international retrospective cohort study. (14th October 2021) - Demolder, A; Muino-Mosquera, L; Pini, A; Evangelista, A; Lopez-Sainz, A; Teixido-Tura, G; Jondeau, G; Szocs, K; Von Kodolitsch, Y; Caruana, M; Buttigieg, L; Cervi, E; et al.
Abstract: Background: Marfan syndrome (MFS), Loeys-Dietz syndrome (LDS) and related heritable thoracic aortic diseases (HTAD) are well-known for their aortic complications. Myocardial dysfunction and arrhythmia are less known in this setting but have been increasingly reported as additional causes of morbidity and mortality. Related to the rarity of the disorders, data on the prevalence of these features and clinical characteristics of the patients are difficult to obtain, calling for a multicentre initiative. Purpose: To study the prevalence of myocardial dysfunction and arrhythmia in patients with HTAD and describe their clinical and genetic profile. Methods: Nine centres from seven countries participated in this multicentre retrospective study. Medical records of patients 12 years or older carrying a (likely) pathogenic variant in the FBN1 gene, LDS genes (TGFBR1, TGFBR2, TGFB2, TGFB3 and SMAD3) or ACTA2 gene were screened. Patients presenting myocardial dysfunction and/or arrhythmia were identified, and clinical and genetic data were collected. Myocardial dysfunction included (a)symptomatic reduced ejection fraction (EF <50% – HFrEF) or symptomatic preserved EF (HFpEF), as documented in the patient charts. Arrhythmias included atrial fibrillation or flutter (AF/AFL), ventricular tachycardia (VT), ventricular fibrillation (VF) and (aborted) sudden cardiac death (SCD) (presumed arrhythmogenic). Results: In total, 3219 patients with HTAD were screened: 2761 with a variant in FBN1, 385 with a variant in one of the LDS genes (TGFBR1, TGFBR2, TGFB2, TGFB3 and SMAD3) and 73 carrying a variant in ACTA2. Myocardial dysfunction and arrhythmia were not reported in patients carrying an ACTA2 variant. Myocardial dysfunction was observed in patients with a variant in FBN1 and the LDS genes, without significant differences in prevalence (2.3% vs. 1.8%, p=0.563). Patients with a variant in the LDS genes presenting myocardial dysfunction were younger than patients carrying a variant in FBN1 (25±11 years vs. 39±17 years, p=0.034). The prevalence of VT/VF/SCD was similar in patients with a variant in one of the LDS genes compared to those with a variant in FBN1 (1.6% vs. 0.8%, p=0.132) and there was no difference in age at time of event (26±13 years vs. 33±14 years, p=0.289). Among patients with a variant in the LDS genes, the prevalence of VT/VF/SCD was highest in patients carrying a variant in the TGFBR2 gene and was significantly higher compared to patients with a variant in FBN1 (3.4% vs. 0.8%, p=0.017). In contrast, AF/AFL was significantly more often reported in patients with a variant in FBN1 compared to those with a variant in one of the LDS genes (1.7% vs. 0.3%, p=0.033). Conclusions: Myocardial dysfunction and arrhythmia are rare features in patients with HTAD. They occur predominantly in patients with a variant in FBN1 and LDS genes, but were not reported in patients carrying a variant in the ACTA2 gene. Further analysis to identify other contributing factors is necessary. FUNDunding Acknowledgement: Type of funding sources: None.